Eksplorasi preferensi pengguna terhadap kondisi pencahayaan dan kondisi spasial serta efeknya terhadap kualitas atmosfer Gereja Katolik - Reforma, Adira Damai; Larasati, Dewi; Kusuma, Hanson Endra (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2024)
The transformations in the design of Catholic church architecture, partly influenced by the Second Vatican Council, have led to notable changes in spatial and lighting conditions. This research endeavors to investigate user preferences concerning lighting and spatial elements in Catholic church buildings. The study adopts a mixed-methods approach, executed in two stages. Data collection involves the utilization of online questionnaires employing a non-random/non-probability sampling method. Subsequent data analysis incorporates principal component analysis, factor analysis, and correlation analysis. Each independent variable is systematically analyzed to discern user preferences. The findings of the study reveal that factors such as color, contrast, visual comfort, lighting hierarchy, visual richness, building age, perceived building shape, verticality, symmetry, and secluded space exert influence on the stimulation of positive and spiritual impressions. The research sheds light on the intricate interplay between architectural elements and user perceptions within the context of Catholic church design, providing valuable insights for further considerations in sustainable and meaningful architectural practices.